Determinan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Banda Sakti Kota Lhokseumawe - Murniati Murniati; Bambang Budi Raharjo (Pusat riset dan Inovasi Nasional, 2025)
World Healt Organization (WHO) data estimates that 175 million children under the age of 1-5 years in the world are affected by malnutrition if efforts to reduce the prevalence of stunting continue continuously, projected to be 157 million by 2025. The purpose of the study was to determine the Determinants of the Incidence of Stunting in Toddlers in the Banda Sakti Health Center Working Area, Lhokseumawe City. The research design uses quantitative with a Cross Sectional approach. The population in this study were all mothers who had toddlers at the Banda Sakti Health Center, Lhokseumawe City, which was 1,672 toddlers, with a sample size of 99 mothers who had toddlers. Data analysis using univariate analysis, bivariate. The results showed that there was an influence of feeding, personal hygiene, parenting, on the incidence of stunting in toddlers in the Banda Sakti Health Center Working Area of Lhokseumawe City. It is recommended that the Banda Sakti Health Center be able to create interesting education for mothers who have toddlers so that they want to bring their children to the Puskesmas or Posyandu so that their children's growth and development are monitored, as well as how to process diverse and nutritious foods so that children get good nutritional intake as an early effort to reduce the incidence of stunting and improve family health.